Joint Consultation by a Neurogeneticist of Movement Disorders and a Psychodynamic Psychotherapist: An Occasion for Subjectivization - Putois, Olivier; Bacqué, Marie-Frédérique; Anheim, Mathieu (Frontiers in Psychology, 2020)
We set out to model a joint therapeutic setting meant to address both medical care and the transferential processes at stake in specialized neurogenetics consultations. Previous authors have explored joint consultation settings with a specialised physician and a psychodynamically oriented psychotherapist; however, few have attempted to provide a model of its transfero-countertransferential dynamics. We aim to do the latter by focusing on a subset of patients to whom such consultations are offered “on the spot”. We want to explore situations in which they initially deny the transference’s contribution to their complaint, when addressing it would instead prove to be beneficial to them, even medically speaking. Standard neurogenetics consultations put the physician in a double-bind position. These patients’ conflicting complaint both manifests transferential expectations and denies them by adhering to medical elements. Since the physician’s challenge is to avoid colluding with the patient’s denial, a joint setting would enable him to address the medical content of the patient’s complaint while simultaneously letting its transferential elements emerge, allowing for the psychotherapist to use them to induce subjective integration (subjectivization). We conceptualize this jointly induced subjectivization by drawing on Fain’s work on primary hystericization of the complaint (inspired by Freud’s late indications). We finish with an example of subjectivization of a family’s complaint based on an adolescent’s limb tremor, which had no genetic or neurological aetiology. Its seemingly conversional nature appeared in light of her father’s reaction to our subjectivizing response: his latent transference was likely underlying his daughter’s symptom.